Determinants and Key Indicators of Concussion in Combat Sport Athletes: A Systematic Review; [Determinantes E Indicadores Clave de la Conmoción Cerebral en Atletas de Deportes de Combate: Una Revisión Sistemática] - Aedo-Munoz, E (Federacion Espanola de Docentes de Educacion Fisica, 2025)
Introduction: Combat sport athletes are more likely to suffer concussions because one of the goals is to knock out an opponent and apply blows during the fight. Objective: To analyze the mechanisms of concussion specific to combat sports and identify the most prevalent signs and symptoms that affect athletes after concussion. Methods: The PRISMA protocol was applied, searches were performed in electronic databases using the descriptors: Athletes, Fighting, Martial Arts, Combat Sports, Concussion, Brain Concussion, Traumatic Brain Injury, Physical Symptoms and Motivational Symptoms. The identification and peer selection process were performed using the Rayyan software. We then extracted the articles which met the eligibility criteria for qualitative analysis, using the Risk of Bias Used for Surveys tool. Results: A total of 912 articles were identified, 90 duplicates and 81 bibliographic reviews, leaving 65 articles for reading the abstracts. Of these, 46 were excluded according to the eligibility criteria, including 19 articles. Regarding exposure to concussion, 70.2% were related to the number of fights performed and 29.8% fighters. The sports modalities were 45.5% MMA, 18.2% boxing, 9.1% taekwondo, 9.1% karate and 9.1% kickboxing. The injuries found were divided into 27.2% traumatic brain injury and 72.8% concussion. According to the signs and symptoms identified, 55.2% were physical and 44.8% motivational. Conclusion: The frequency of fights is a determining factor for the incidence of concussions in combat sport athletes and the post-concussion symptoms showed significant physical and motivational manifestations, which represent barriers to the technical-tactical development of athletes. © 2025 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.